Correlates of objectively measured sedentary behavior in cancer patients with brain metastases: an application of the theory of planned behavior. Issue 7 (29th July 2014) - Lowe, Sonya S.; Danielson, Brita; Beaumont, Crystal; Watanabe, Sharon M.; Baracos, Vickie E.; Courneya, Kerry S.
Abstract Objective The aim of this study is to examine the demographic, medical, and social‐cognitive correlates of objectively measured sedentary behavior in advanced cancer patients with brain metastases. Methods Advanced cancer patients diagnosed with brain metastases, aged 18 years or older, cognitively intact, and with palliative performance scale greater than 30%, were recruited from a Rapid Access Palliative Radiotherapy Program multidisciplinary brain metastases clinic. A cross‐sectional survey interview assessed the theory of planned behavior variables and medical and demographic information. Participants wore activPAL™ (PAL Technologies Ltd, Glasgow, United Kingdom) accelerometers recording time spent supine, sitting, standing, and stepping during 7 days encompassing palliative whole brain radiotherapy treatments. Results Thirty‐one patients were recruited. Correlates of median time spent supine or sitting in hours per day were instrumental attitude (i.e., perceived benefits) of physical activity (r = −0.42; p = 0.030) and affective attitude (i.e., perceived enjoyment) of physical activity (r = −0.43; p = 0.024). Moreover, participants who sat or were supine for greater than 20.7 h per day reported significantly lower instrumental attitude (M = 0.7; 95% CI = 0.0–1.4; p = 0.051) and affective attitude (M = 0.7; 95% CI = 0.0–1.4; p = 0.041). Finally, participants who were older than 60 years of age spent more time sitting or being supine. Conclusions Instrumental attitude and affective attitude were the strongest correlates of objectively measured sedentary behavior. This information could inform intervention studies to increase physical activity in advanced cancer patients with brain metastases. Copyright © 2014 John Wiley & Sons, Ltd.